Combined conventional thermal and microwave drying process for typical Chinese lignite. Issue 7 (19th May 2019) - Ge, Jin; He, Yong; Zhu, Yanqun; Wang, Zhihua; Zhang, Kang; Huang, Zhenyu; Cen, Kefa
Abstract: A combined conventional and microwave drying process for Ximeng lignite was investigated in this paper. Samples were firstly dehydrated by hot air to achieve a conversion moisture content, and then were managed to final moisture content by microwave drying. Results showed that the drying rate was significantly improved in the decreasing rate period by microwave drying, approximately 3–5 times faster than that of conventional drying. Finally, the orthogonal test was used to clarify the effects of each factor on the energy consumption, and the magnitude ranking order was conversion moisture content > microwave power > hot air temperature.